(untitled) (Encuentros, 2020)
The processing of textuality in the native language curriculum policy in Colombia This paper proposes a critical reflection about an approach to textual linguistics in the Curricular Guidelines of the Spanish Language. The aim is to contribute for the revisions that the pedagogical academy has been asking about the current curricular policy in this area, two decades after its last general reform. It deals with the problem of textuality in the pedagogical document referred to, as well as the reduction of textuality to the notion of textual competence. Is necessary to reorient curricular guidelines towards a conception of textuality more concerned with the use of language as a social, cultural, historical and political activity Key words: linguistic education, education by competences, applicationism, didactic.